Synergy between Police Law and Customary Law in Resolving Social Conflicts in West Papua - Alwafi, Muhammad (Universitas Syiah Kuala, 2025)
This study aims to analyze the synergy between police law and customary law in resolving social conflicts in West Papua. The approach used is juridical-sociological, with a descriptive-analytical method, combining interviews, observations, and legal document studies, including Perpol No. 8 of 2021 concerning restorative justice and the Papua Special Autonomy Law No. 21 of 2001/Law No. 2 of 2021. The research locations include Manokwari, Sorong, and Fakfak districts, with informants consisting of police officers, traditional leaders, and affected communities. The results of the study show that social conflicts in West Papua, especially between indigenous communities, can be resolved more effectively through the synergy of police law and customary law. The police act as facilitators of restorative deliberations, while customary courts emphasize deliberation, consensus, and the restoration of social relations. The integration of these two legal systems results in community-accepted conflict resolution, increases compliance of perpetrators, and maintains social stability. This multi-dimensional approach is in accordance with the theory of restorative justice and living law, which emphasizes the restoration of social relations as well as the recognition of the legal norms that live in society. This study concludes that the harmonization of formal law and customary law in West Papua is an important strategy in realizing substantive justice, reducing the burden of cases in formal courts, and maintaining social harmony between communities. These findings can be a reference for police officers, local governments, and traditional leaders in developing standard operational procedures for restorative-based conflict resolution in accordance with local wisdom.